Study on Identifying the Cattle Diseases Using Artificial Intelligence Techniques - H. S. Anupama; B. A. Usha; M. Aishwarya (New Visions in Science and Technology Vol. 4, 2021)
One of the largest sectors in India is a livestock sector. It has 56.7% of world’s buffaloes, 12.5% cattle, 20.4% small ruminants, 2.4% camel, 1.4% equine, 1.5% pigs and 3.1% poultry. The average yield which we get from animals in terms of milk or meat is 20-60% lesser than the global average. Their production potential is not fully developed because of the lack of the breeding, feeding, health and the management issues. And also because of the diseases the animals do get like Brucellosis, Swine fever and so on. The veterinary support for this is insufficient. This paper focuses on identifying these diseases from cattle using some Artificial and Machine Learning techniques. In this work, four major diseases are addressed FMD Foot and Mouth disease, HS, BQ Black Quarter, and Anthrax. A mobile app is being developed to detect the diseases through the camera. Data science and deep learning technology is used to detect, to store and to predict the disease. Once the result is obtained from the data, those results could be shared with doctors nearby through the mobile phone. Based on doctor’s advice some medicines could be given by the farmers itself. As a result, one doctor can serve more patients virtually.